10-Hydroxy Decanoic Acid-Based Vesicles as a Novel Topical Delivery System: Would It Be a Better Platform Than Conventional Oleic Acid Ufasomes for Skin Cancer Treatment? - Bassant Atef; Rania A. H. Ishak; Sabry S. Badawy; Rihab Osman (MDPI AG, 2023)
10-hydroxy decanoic acid (HDA), a naturally derived fatty acid, was used for the preparation of novel fatty acid vesicles for comparison with oleic acid (OA) ufasomes. The vesicles were loaded with magnolol (Mag), a potential natural drug for skin cancer. Different formulations were prepared using the thin film hydration method and were statistically evaluated according to a Box-Behnken design in terms of particle size (PS), polydispersity index (PDI), zeta potential (ZP), and entrapment efficiency (EE). The ex vivo skin permeation and deposition were assessed for Mag skin delivery. In vivo, an assessment of the optimized formulae using 7,12-dimethylbenz[a]anthracene (DMBA)-induced skin cancer in mice was also conducted. The PS and ZP of the optimized OA vesicles were 358.9 ± 3.2 nm and −82.50 ± 7.13 mV compared to 191.9 ± 6.28 nm and −59.60 ± 3.07 mV for HDA vesicles, respectively. The EE was high (>78%) for both types of vesicles. Ex vivo permeation studies revealed enhanced Mag permeation from all optimized formulations compared to a drug suspension. Skin deposition demonstrated that HDA-based vesicles provided the highest drug retention. In vivo, studies confirmed the superiority of HDA-based formulations in attenuating DMBA-induced skin cancer during treatment and prophylactic studies.